Analysis of Organizational Culture and Employee Performance Appreciation with Work Motivation as a Mediating Variable at the National Narcotics Agency of North Sumatra Province - Kurniawan, Wawan; Indrawan, Muhammad Isa; Rahayu, Sri (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of organizational culture and rewards on employee performance with work motivation as a mediating variable at the National Narcotics Agency (BNN) of North Sumatra Province. Employee performance is an important factor in achieving organizational strategic goals, especially at the BNN, which faces the complexity of narcotics circulation and demands for quality rehabilitation services. Organizational culture and rewards are expected to influence employee performance directly and through work motivation. The type of research used is quantitative with a survey approach. The research population consists of all 84 permanent employees of the North Sumatra Provincial BNN. Data were collected through questionnaires and analyzed using Partial Least Squares (PLS). The results showed that organizational culture had a positive and significant effect on employee performance and work motivation. Rewards had a positive and significant effect on work motivation but did not significantly affect employee performance directly. Work motivation played a significant role as a mediator, so that organizational culture and rewards could improve employee performance through work motivation. The R² value shows that organizational culture, rewards, and work motivation can explain 91.9% of the variation in employee performance. These findings imply that the North Sumatra Provincial Narcotics Agency needs to strengthen its organizational culture, implement a fair reward system, and encourage employee work motivation through independence, autonomy, and recognition of their contributions. This approach is expected to improve employee performance consistently and professionally.